Comparative Study of Laboratory Management: Study Case of Ujung Pandang State Polytechnic and Makassar Merchant Marine Polytechnic - Hasiah, Hasiah; Risal, Syah; Nari, Henny P; Sirman, Mahadir (INTEK: Jurnal Penelitian, 2022)
The laboratory role is huge in determining the quality of education because the laboratory produces proud scientific works, which other institutions cannot make. To get quality universities, laboratories are a priority. The laboratory is an integral part of the academic field. Laboratory management needs to be aligned with educational planning (programs and budgets). This research was carried out at the Ujung Pandang State Polytechnic (PNUP) and the Merchant Marine Polytechnic (PIP) Makassar. This research method is a comparative research type. Data collection techniques used are observation, interviews, and documentation. The method of analysis was using quantitative descriptive analysis. The results show that the Ujung Pandang State Polytechnic has a laboratory with laboratory management that is very concerned about the curriculum/module/syllabus, which is updated regularly. Comparing management laboratory includes a) understanding and access freely the modules for students, b) online laboratory schedule, c) the ratio of teachers according to the Higher Education standard of 1 : 8. For Laboratory Management at the Ujung Pandang State Polytechnic using the SOP for practicum implementation managed by a laboratory technician who has a certificate for the use of laboratory equipment. Some technicians are always available at the laboratory. The ideal laboratory to consider the ratio between the area of the laboratory room and the number of practitioners, the balance between teachers and students, the proportion of equipment, facilities, room conditions, and the equipment used condition.